A CHO-Based Cell-Free Dual Fluorescence Reporter System for the Straightforward Assessment of Amber Suppression and scFv Functionality - Krebs, Simon K.; Rakotoarinoro, Nathanaël; Stech, Marlitt; Zemella, Anne; Kubick, Stefan (Frontiers in Bioengineering and Biotechnology, 2022)
Incorporation of non-canonical amino acids (ncAAs) with bioorthogonal reactive groups by amber suppression allows the generation of synthetic proteins with desired, novel properties. Such modified molecules are in high demand for basic research and therapeutic applications such as cancer treatment and in vivo imaging. The positioning of the ncAA-responsive codon within the protein’s coding sequence is critical in order to maintain protein function, achieve high yields of ncAA-containing protein and allow effective conjugation. Cell-free ncAA incorporation is of particular interest due to the open nature of cell-free systems and their concurrent ease of manipulation. In this study, we report a straight-forward workflow to inquire ncAA positions in regard to incorporation efficiency and protein functionality in a Chinese hamster ovary (CHO) cell-free system. As a model the well-established orthogonal translation compounds Escherichia coli tyrosyl-tRNA synthetase (TyrRS) and tRNATyrCUA were used to site-specifically incorporate the ncAA p-azido-L-phenylalanine (AzF) in response to UAG codons. Seven ncAA sites within an anti-Epidermal Growth Factor Receptor (EGFR) single-chain variable fragment (scFv) N terminally fused to the red fluorescent protein mRFP1 and C terminally fused the green fluorescent protein sfGFP were investigated for ncAA incorporation efficiency and impact on antigen binding. The characterized cell-free dual fluorescence reporter system allows screening for ncAA incorporation sites with high incorporation efficiency that maintain protein activity. It is parallelizable, scalable and easy to operate. We propose that the established CHO-based cell-free OTS can be of particular interest for the development of antibody-drug conjugates (ADCs).